• Shuffle
Toggle On
Toggle Off
• Alphabetize
Toggle On
Toggle Off
• Front First
Toggle On
Toggle Off
• Both Sides
Toggle On
Toggle Off
Toggle On
Toggle Off
Front

### How to study your flashcards.

Right/Left arrow keys: Navigate between flashcards.right arrow keyleft arrow key

Up/Down arrow keys: Flip the card between the front and back.down keyup key

H key: Show hint (3rd side).h key

A key: Read text to speech.a key

Play button

Play button

Progress

1/137

Click to flip

### 137 Cards in this Set

• Front
• Back
 A is 3 more (greater)than B A=B+3 A is less (fewer) than B A=B-3 A is 2/3 more(greater) than B A=B+2/3B = B(1+2/3) A is 2/3 less(fewer) than B A=B-2/3B = B(1-2/3) A is percent more (greater) than B A=B+50/100B =B(1+50/100) A is percent less (fewer) than B A=B(1-50/100) B 가 A 보다 300% 만큼클경우, B가A의 4배이다 B=A(1+300/100)=4A A is 3 times as many (much) as B = 3 times as many (much) A as B A=3B A is no more than B A is less than or equal to B A is at most B A>=B A is no less than B A is more than or equal to B A is at least B A<=B 정수 X의개수 a=0 x is? 0보다 클땐 항상 바깥범위 x>3 x<1 (x-1)(x-3)<0 x is ? 0 보다 작을땐 사이 범위 1 0 postive slope function is inc dy/dx <0 negative slope function is dec for f(x) f''(x) = d^2/dx^2 f(x) =d/dx f'(x) second derivitive tell concave up(local min) or down (local max) f''(x) >0 concave up (local min) f''(x)<0 concave down (local max) f''(x) = 0 constant slope d/dx [f(x)/g(x)] = quotient rule g(x)f'(x)-f(x)g'(x)/g^2(x) velocity v(t) first derivativ of position (a(t) acceleration (how fast speed change) a(t) second derivative of position first derivative of velocity d/dx sin(x) cos(x) 1 1 is der of x d/dx cos (x) -sin (x) 1 1 is der of x d/dx tan (x) sec^2(x) 1 1 is der of x d/dx csc(x) -csc(x)cot(x) 1 1 is der of x d/dx sec (x) sec(x)tan(x) 1 1 is der of x d/dx cot(x) -csc^2(x) 1 1 is der of x product rule d/dx[f(x)g(x)]=f(x)g'(x)+f(x)g'(x) f(x)g'(x)+f(x)g'(x) if f(x)=e^x then f'(x) f'(x) = e^x if f(x)=ln(x) then f'(x) f'(x) = 1/x [ = intergral [cos(x)dx sin (x) + C [ = intergral [sin(x)dx -cos (x) + c [ = intergral [sec^2(x) tan (x) +c [ = intergral [csc(x)cot(x)dx -csc(x) +c [ = intergral [sec(x)tan(x)dx =sec(x)+c [ = intergral [csc^2(x) dx -cot(x)+c